The failure of the new Erzincan project in light of party-state relations at the local level - Mutlu, Elşen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Erzincan Earthquake in 1939 is one of the greatest natural disaster in the history of the Turkish Republic. More than thirty thousand people have died and city of Erzincan was wiped out of the map. As a response to it, construction of a new modern city which would provide the necessary conditions to live a civilized life for the residents of Erzincan was planned by the single party regime. Even though it tends to be seen as an omnipotent force, single party regime had its limits and they became apparent when it failed to undertake a task as ambitious as building a new city from scratch in Erzincan. Ascribing this failure just to external factors, which were out of the control of the single party regime such as the Second World War, only partially explains the story. The limits which prevented it to materialize New Erzincan were not solely external, but also emanated from the very feature that made this regime so unique in Turkish nation state’s history: the relationship between state and party. This uneasy relationship was far from being smooth unlike what is often tend to be envisioned. In this thesis it is argued that, the lack of harmony between the local party organization and local state bureaucracy that reflected itself in the shape of a vicious conflict between the governor and the alliance formed by the head of local party organization and the party inspector, was one of the primary reasons that led the project to its demise.
Keywords: Earthquakes -- Turkey -- Erzincan.